COVID-19 face masks: A new source of human and environmental exposure to organophosphate esters. (September 2021) - Fernández-Arribas, J.; Moreno, T.; Bartrolí, R.; Eljarrat, E.
Graphical abstract: Highlights: OPEs were detected for the first time in face masks at levels up to 28 µg/mask. KN95 masks presented the highest OPE values. A 10% of OPE content in masks was inhaled during their use. Non-CR and CR risks were much lower than the threshold risk values. In terms of environmental impact, the best option is reusable masks. Abstract: For the first time, organophosphate ester (OPE) content was studied in different types of surgical, self-filtering (KN95, FFP2, and FFP3) and reusable face masks used for COVID-19 prevention. OPEs were detected in all mask samples, although in highly variable amounts which ranged from 0.02 to a maximum of 27.7 µg/mask, with the highest mean concentrations obtained for KN95 masks (11.6 µg/mask) and the lowest for surgical masks (0.24 µg/mask). Twelve out of 16 tested analytes were detected, with TEP, TPHP, TNBP, TEHP and TClPP being the most common OPEs as well as present at the highest concentrations. The non-carcinogenic and carcinogenic risks of OPE inhalation were calculated as being always several orders of magnitude lower than threshold levels, indicating that the use of face masks is safe with regard to OPE contamination. However, given the wide range of OPEs observed in different masks, it can be concluded that some masks (e.g. reusable) are less OPE-contaminated than others (e.g. KN95). With regard to environmental pollution, the disposal of billions of face masks is adding to the already substantial levels of microplastics and associated toxic additives worldwide, an impact that is lessened by use of reusable masks, which also have the lowest economic cost per user. However, in situations of relatively high risk of viral inhalation, such as poorly ventilated indoor public spaces, we recommend the use of FFP2 masks.